Water Infiltration Policy for Urban Flood Management - Aufa, Fushshilati; Widiyanti, Amalika; Azhar Syahdan, Taufail; Sutrisno, Endang; Krisnandar, Iis (CV. Green Publisher Indonesia, 2024)
This research was conducted to determine the implementation of water absorption policies for flood management in urban areas, especially in the city of Cirebon at the Cirebon City Public Works and Spatial Planning (DPUPR) department. The research approach used is normative juridical, conceptualizing law as written norms so that this research emphasizes studies in the form of legislative products, namely those that regulate water absorption such as regional regulation number 38 of 2019 concerning the implementation of groundwater conservation through infiltration wells and infiltration holes. biopore. Policy implementation in flood management by the Cirebon City PUPR Service has included handling floods and puddles as a priority in the Regional Government Work Plan (RKPD) for 2025. For handling urban drainage, the PUPR Service's work target is to reach up to 83% by 2024, and 86% for 2025, and 89% for 2026. One of the strategies taken includes the creation of retention ponds, absorption wells and eco-drainage. However, there are still several obstacles in implementing this policy, such as limited resources and lack of community participation. To overcome these obstacles, efforts need to be made such as increasing the budget, providing adequate human resources, and educating the public about the importance of water absorption. Overall, the implementation of the water absorption policy for flood management in Cirebon City has shown a positive direction. With continued efforts and collaboration from various parties, it is hoped that this policy can be more effective in minimizing the risk of flooding in urban areas.